A case of aortic dissection presenting with a transient ischemic attack - Kara, Fatma; Göl, Mehmet Fatih; Varlıbaş, Ayhan (Journal of Surgery and Medicine, 2021)
Aortic dissection (AD) is the rupture of the aortic intima, separation of the tunica media and blood filling into the wall. It is an exceedingly rare life-threatening disease with a high mortality rate. The pathogenesis of AD is multifactorial and aortic diseases such as aortic dilatation, aneurysm, ectasia, arteritis, bicuspid aorta, aortic arch hypoplasia, coarctation, chromosomal abnormalities (Turner, Noonan), connective tissue disease (Marfan, Ehlers-Danlos) are well-defined risk factors for aortic dissection. Chest pain is the most common clinical presentation of AD. Cardiovascular and neurological systems are often affected. Patients with AD may also present with unexpected symptoms such as syncope, hemiparesis-hemiplegia, paraparesis-paraplegia, myocardial infarction, dysphagia, and side pain. In this article, we present a patient who presented to the emergency department with neck pain, amaurosis fugax, and hypotension, who was admitted to the neurology ward with suspicion of transient ischemic attack and diagnosed with aortic dissection.